2007
DOI: 10.1021/ie061429n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Size Distribution of Commercial Activated Carbon Fabrics on the Adsorption of CWA Simulants from the Liquid Phase

Abstract: The use of hydrofluoroether liquid wetted wipes for the decontamination of sensitive equipment is attracting great interest. Contacting the contaminated equipment with such wipes results in the rapid removal of surface contaminants. Because adsorption from the liquid phase involves larger molecules than those found in the gas phase, the pores in the activated carbon needed to capture contaminants require pores with diameters above the micropore range (diameters <2 nm). In this work, the effects of the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 1 publication
1
35
0
Order By: Relevance
“…The total pore volume of KNOSC is ≈1.39 cm 3 g −1 , where the mesopore volume is 0.94 cm 3 g −1 , ≈67% of the total volume. The volumetric percentage of mesopores are much higher than that of commercial activate carbon (0.4 cm 3 g −1 for total pore volume and 0.05 cm 3 g −1 for mesopore volume) . The results confirmed that the KNOSC possess a multiscale pore system involving macropores, mesopores and micropores.…”
Section: Resultssupporting
confidence: 54%
“…The total pore volume of KNOSC is ≈1.39 cm 3 g −1 , where the mesopore volume is 0.94 cm 3 g −1 , ≈67% of the total volume. The volumetric percentage of mesopores are much higher than that of commercial activate carbon (0.4 cm 3 g −1 for total pore volume and 0.05 cm 3 g −1 for mesopore volume) . The results confirmed that the KNOSC possess a multiscale pore system involving macropores, mesopores and micropores.…”
Section: Resultssupporting
confidence: 54%
“…Based on this study, the inclusion of chemical neutralization in decontamination line procedures does not significantly reduce chemical exposure risks to personnel doffing PPE.The type of physical removal employed, and the sequence of removal and neutralization in a decontamination line bears further study. For example, an initial reduction of the amount of chemical that is present on a PPE or related material through physical removal such as dry decontamination (with e.g., nonwoven dry fabric pads[20,21]), would significantly ease the stoichiometric contaminant/decontaminant burden to use larger amounts of liquid decontaminant. However, even marginal decreases in contamination due to neutralization chemistries can be important prior to PPE doffing.…”
mentioning
confidence: 99%
“…This tendency is attributed to the increase of active metal species which enhances the degradation of CWAs. Subsequently, loading of Zr(OH) 4 above 8% does not have a significant effect on the degradation of sarin as higher loading percentage of Zr(OH) 4 may block the pores of W-ACF, which lead to low accessibility of CWA sarin with Zr(OH) 4 39 , 83 . Hence, 6% Zr(OH) 4 loading on W-ACF was employed in all further degradation studies of sarin and soman.…”
Section: Resultsmentioning
confidence: 99%